2015
DOI: 10.1038/ncomms9643
|View full text |Cite
|
Sign up to set email alerts
|

Multimaterial magnetically assisted 3D printing of composite materials

Abstract: 3D printing has become commonplace for the manufacturing of objects with unusual geometries. Recent developments that enabled printing of multiple materials indicate that the technology can potentially offer a much wider design space beyond unusual shaping. Here we show that a new dimension in this design space can be exploited through the control of the orientation of anisotropic particles used as building blocks during a direct ink-writing process. Particle orientation control is demonstrated by applying low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
555
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 695 publications
(576 citation statements)
references
References 40 publications
3
555
0
Order By: Relevance
“…[59] A more universal and controllable method, however, is magnetically assisted slip casting (MASC) [60] or magnetically assisted 3D printing. [61,62] Ferrand et al [60] demonstrated that alumina nanoplatelets coated with superparamagnetic iron oxide nanoparticles could be assembled by applying an external rotating magnetic field. As shown in Figure 5A, the suspension was placed in a gypsum mold to remove solvent to form a layer of jammed and fixed assembled nanoplatelets during the slip casting process.…”
Section: Mimicking Of Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…[59] A more universal and controllable method, however, is magnetically assisted slip casting (MASC) [60] or magnetically assisted 3D printing. [61,62] Ferrand et al [60] demonstrated that alumina nanoplatelets coated with superparamagnetic iron oxide nanoparticles could be assembled by applying an external rotating magnetic field. As shown in Figure 5A, the suspension was placed in a gypsum mold to remove solvent to form a layer of jammed and fixed assembled nanoplatelets during the slip casting process.…”
Section: Mimicking Of Architecturementioning
confidence: 99%
“…Kokkinis et al [61] demonstrated that composites with diverse components, complex shape, and varying orientation of building blocks could be fabricated by multimaterials' magnetically assisted 3D (MM-3D) printing. As shown in Figure 5C, their composite was printed with two kinds of materials: texturing ink (beige) with alumina platelets and shaping ink (gray).…”
Section: Mimicking Of Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced/adapted with permission from refs. [58,[79][80][81][82][83][84] www.advancedsciencenews.com www.aem-journal.com printed scaffolds, thereby making them electrically stimulating for the cells. [56] It is worth noting that nanomaterials can also be attached to the surface of an already 3D printed structure, in order to either add functionality or improve a desired performance such as increase bioactivity in biomedical and lab-on-a-chip devices.…”
mentioning
confidence: 99%
“…The International Technology Roadmap for Semiconductors (ITRS 2.0, see http://www.itrs2.net/itrs-reports.html) calls for '3D Power Scaling' as the next phase of silicon integrated circuit technology. These technologies, coupled with recent advances in 3D printing 19,20 and surface mounting technologies (such as magnetic field assisted assembly) 21 are anticipated to be the next enabler of manufacturing systems-on-a-chip, XYZ-on-a-chip, lab-on-a-chip, etc.…”
mentioning
confidence: 99%